2018
DOI: 10.1103/physreva.98.053850
|View full text |Cite
|
Sign up to set email alerts
|

Towards optical-frequency-comb generation in continuous-wave-pumped titanium-indiffused lithium-niobate waveguide resonators

Abstract: Much progress, both experimentally and theoretically, has recently been made towards optical frequency comb generation from continuously pumped second-order nonlinear systems. Here, we present observations towards finding an integrated solution for such a system, using a titanium indiffused lithium niobate waveguide resonator. These results are compared to recently developed theory for equivalent systems. The system is seen to exhibit strong instabilities, which require further investigation in order to fully … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Scaling the resonator to micrometric size may be beneficial for quadratic combs, allowing for a dramatic reduction of threshold power and a flexible management of the dispersion through a geometric design, allowing for a broader comb emission. As a matter of fact, direct generation of quadratic frequency combs has been very recently observed in chip-scale lithium niobate devices, such as periodically poled linear waveguide resonators [74,75], or exploiting naturally phase-matched SHG in whispering-gallery-mode resonators [76,77].…”
Section: Perspectivesmentioning
confidence: 99%
“…Scaling the resonator to micrometric size may be beneficial for quadratic combs, allowing for a dramatic reduction of threshold power and a flexible management of the dispersion through a geometric design, allowing for a broader comb emission. As a matter of fact, direct generation of quadratic frequency combs has been very recently observed in chip-scale lithium niobate devices, such as periodically poled linear waveguide resonators [74,75], or exploiting naturally phase-matched SHG in whispering-gallery-mode resonators [76,77].…”
Section: Perspectivesmentioning
confidence: 99%
“…We can observe from the mode profiles that the optical mode of pump is first confined into the SixNy waveguide, and then lifted to PPLN region in section C. The SPDC light generated from the PPLN region goes down to the SixNy waveguide for convenient output with over 92.3% transmission. Thanks to the high index contrast structure and submicrometer thickness of the LN thin film, the waveguide modes are tightly confined into a mode area that is smaller than that achieved with proton exchange or Ti indiffusion [25,26]. This mode confinement feature directly relates to the refractive index of SixNy.…”
Section: Waveguide Structure Designmentioning
confidence: 99%
“…Soon thereafter, in 2007, OFCs were demonstrated in microresonators pumped by a continuous-wave (cw) laser, exploiting the third-order nonlinear susceptibility χ (3) , in so called Kerr combs [7,8]. Recent theoretical studies and experimental investigations have demonstrated frequency comb generation also in quadratic nonlinear optical cavities, realizing quadratic frequency combs [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. These sources provide an interesting alternative to traditional comb generation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These sources provide an interesting alternative to traditional comb generation techniques. They offer numerous advantages in terms of low pump power requirements, spectral versatility, and potential for miniaturization of the device [17][18][19][20][21][22][23]. Interestingly, they can generate simultaneous combs in different spectral ranges.…”
Section: Introductionmentioning
confidence: 99%